Chemical synthesis and mechanism of a natural product from endolichenic fungus with a broad-spectrum anti microorganism activity - Zhou, Xuan; Wang, Ming-Yi; Cao, Qian-Ping; Yang, Ze; Meng, Qing-Feng; Fu, Shao-Bin (Frontiers in Microbiology, 2023)
Background The antibiotic resistance in various bacteria is consistently increasing and is posing a serious threat to human health, prompting the need for the discovery of novel structurally featured natural products with promising biological activities in drug research and development. Endolichenic microbes have been proven to be a fertile source to produce various chemical components, and therefore these microbes have been on a prime focus for exploring natural products. In this study, to explore potential biological resources and antibacterial natural products, the secondary metabolites of an endolichenic fungus have been investigated. Methods The antimicrobial products were isolated from the endolichenic fungus using various chromatographic methods, and the antibacterial and antifungal activities of the compounds were evaluated by the broth microdilution method under in vitro conditions. The antimicrobial mechanism has been discussed with measuring the dissolution of nucleic acid and protein, as well as the activity of alkaline phosphatase (AKP) in preliminary manner. Chemical synthesis of the active product compound 5 was also performed, starting from commercially available 2,6-dihydroxybenzaldehyde through a sequence of transformations that included methylation, the addition of propylmagnesium bromide on formyl group, the oxidation of secondary alcohol, and the deprotection of methyl ether motif. Results Among the 19 secondary metabolites of the endolichenic fungus, Daldinia childiae (compound 5) showed attractive antimicrobial activities on 10 of the 15 tested pathogenic strains, including Gram-positive bacteria, Gram-negative bacteria, and fungus. The Minimum Inhibitory Concentration (MIC) of compound 5 for Candida albicans 10213, Micrococcus luteus 261, Proteus vulgaris Z12, Shigella sonnet, and Staphylococcus aureus 6538 was identified as 16 μg/ml, whereas the Minimum Bactericidal Concentration (MBC) of other strains was identified as 64 μg/ml. Compound 5 could dramatically inhibit the growth of S. aureus 6538, P. vulgaris Z12, and C. albicans 10213 at the MBC, likely affecting the permeability of the cell wall and cell membrane. These results enriched the library of active strains and metabolites resources of endolichenic microorganisms. The chemical synthesis of the active compound was also performed in four steps, providing an alternative pathway to explore antimicrobial agents.